Investigation of the Online Game Addiction Level, Sociodemographic Characteristics and Social Anxiety as Risk Factors for Online Game Addiction in Middle School Students - KARAKOÇ, AYŞE; ÜNSAL, GÜL; CAN GÜRKAN, ÖZLEM; KARACA, SEMRA (SPRINGER, 2020)
The purpose of this study was to investigate the online game addiction (OGA) level and the risk factors involved in OGA among middle school students. The descriptive cross-sectional study was conducted at seven middle schools in the province of Istanbul. The data were collected with a questionnaire, the Computer Game Addiction Scale for Children (CGASC) and the Social Anxiety Scale for Children (SASC); 1174 students who played online computer games were included in the study. It was found that 5.7% of the sample group were addictive users, that 44% were problematic users and that an older age, a higher level of social anxiety (SA), having a mother who is employed, having parents who completed high school or a higher level of education, and the time spent on the computer are risk factors for OGA.
Keywords: Student; Risk factors; Online game addiction; Social anxiety; INTERNET GAMING DISORDER; ADOLESCENTS; LONELINESS; PREVALENCE; SYMPTOMS; BEHAVIOR; GENDER; USERS